DBS of the ANT for refractory epilepsy: A single center experience of seizure reduction, side effects and neuropsychological outcomes - Olaciregui Dague, Karmele; Witt, Juri-Alexander; von Wrede, Randi; Helmstaedter, Christoph; Surges, Rainer (Frontiers in Neurology, 2023)
Objective: Evaluation of the antiseizure efficacy, side effects and neuropsychological effects of DBS-ANT. Deep brain stimulation (DBS) of the anterior nucleus of the thalamus (ANT) is a treatment option for patients with difficult-to-treat epilepsy. Though several works outline the cognitive and/or mood effects of DBS-ANT for the treatment of epilepsy, data on the intersection between antiseizure efficacy, cognitive and undesired effects are scarce. Methods: We retrospectively analyzed the data of our cohort of 11 patients. Post-implantation seizure frequencies were measured at 6 months, 12 months and last follow-up, as well as averaged throughout follow-up. These values were then compared with mean seizure frequencies in the 6 months before implantation. To address acute cognitive effects of DBS a baseline assessment was performed after implantation and before stimulation, and a follow-up assessment was conducted under DBS. The long-term effects of DBS on cognition were assessed by comparing the preoperative neuropsychological profile with a long-term follow-up under DBS. Results: In the entire cohort, 54.5% of patients were responders, with an average seizure reduction of 73.6%. One of these patients achieved temporary seizure freedom and near-total seizure reduction during the entire follow-up. Seizure reduction of <50% was achieved in 3 patients. Non-responders suffered an average seizure increase of 27.3%. Eight of twenty-two active electrodes (36,4%) were off-target. Two of our patients had both electrodes implanted off-target. When removing these two patients from the analysis and averaging seizure frequency during the entire follow-up period, four patients (44.4%) were responders and three experienced a seizure reduction of <50%. Intolerable side effects arose in 5 patients, mostly psychiatric. Regarding acute cognitive effects of DBS, only one patient showed a significant decline in executive functions. Long-term neuropsychological effects included significant intraindividual changes in verbal learning and memory. Figural memory, attention and executive functions, confrontative naming and mental rotation were mostly unchanged, and improved in few cases. Significance: In our cohort, more than half of patients were responders. Psychiatric side effects seem to have been more prevalent compared to other published cohorts. This may be partially explained by a relatively high occurrence of off-target electrodes.